2023
DOI: 10.1128/spectrum.03356-22
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Canada Variability in Blood Donor SARS-CoV-2 Seroprevalence by Social Determinants of Health

Abstract: Canadian blood donors are a healthy adult population that shows clear disparities associated with racialization and material deprivation. This underscores the pervasiveness of the socioeconomic gradient on SARS-CoV-2 infections in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Samples were randomly selected for serologic testing from approximately last two weeks of each month from January 2021 to December 2021 and from all weeks from January 2022 to November 2022. As previously described, 13 a straight random sample was applied until June 2021, after which stratification by age group was applied to enable a smaller monthly sample size. Samples were tested for anti-nucleocapsid antibodies using the Roche Elecsys ® Anti-SARS-CoV-2 assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were randomly selected for serologic testing from approximately last two weeks of each month from January 2021 to December 2021 and from all weeks from January 2022 to November 2022. As previously described, 13 a straight random sample was applied until June 2021, after which stratification by age group was applied to enable a smaller monthly sample size. Samples were tested for anti-nucleocapsid antibodies using the Roche Elecsys ® Anti-SARS-CoV-2 assay.…”
Section: Methodsmentioning
confidence: 99%
“… 12–15 Reports found that anti-N seropositivity was associated with younger age, belonging to a visible minority, being from a more materially deprived neighbourhood, or from a less socially deprived neighbourhood. 12 , 13 These findings help to identify disparities in SARS-CoV-2 infection and can inform resource allocation. However, the evolution of correlates of seropositivity through Omicron has not been analysed, urban and rural differences in seropositivity have not been explored, and geographic variability in seropositivity at the sub-provincial level has not been published.…”
Section: Introductionmentioning
confidence: 95%